Comparative Evaluation of New Resins Versus Commercially Available Resins in Solid-Phase Peptide Synthesis - Jahic,Kemal (2025)
Solid-phase peptide synthesis (SPPS) is the most widely used method for producing synthetic peptides, with the solid support-known as the resin-being a critical component of the process. Redstone Separations AB, a company based in Lomma, Sweden, has developed new SPPS resins and aims to evaluate their performance compared to commercially available alternatives. In this study, Redstone ́s resins were assessed by synthesizing three peptides: Neurotensin, GLP-1 (at both room temperature and elevated temperature), and an RGD-peptide. These peptides were synthesized using SPPS followed by post-synthetic modifications for the RGD peptide, and resulting products were evaluated for yield and purity. The results showed that for Neurotensin, some Redstone ́s resins outperformed some commercial resins, although the highest performance was still observed with the commercial resins. In the synthesis of GLP-1, both at room and elevated temperatures, commercial resins yielded better results, but Redstone ́s resins were comparable. The synthesis of the RGD-peptide was unsuccessful for both Redstone and commercial resins, as the obtained amounts were too low to quantify and the right peptide was not seen for some of the resins. Overall, the results demonstrate that Redstone ́s resins are capable of producing peptides in reasonable yields and purities. Although further optimization is needed to reach or surpass the performance of established commercial resins, these findings are promising, especially considering that Redstone is newly established maker of SPPS resins in the market and that it was shown that the resins worked for SPPS overall.
Keywords: Organic Chemistry; Peptide Synthesis; Polymer Synthesis; Peptide Chemistry; On-resin modifications